Biocatalytic Approaches to the Enantiomers of Wieland–Miescher Ketone and its Derivatives. Issue 29 (6th April 2021) - Bertuletti, Susanna; Bayout, Ikram; Bassanini, Ivan; Ferrandi, Erica E.; Bouzemi, Nassima; Monti, Daniela; Riva, Sergio
Abstract: Biocatalytic approaches have been investigated in order to isolate the enantiomers of Wieland–Miescher ketone (1 ) and of its alcoholic derivatives ( cis ‐2 and trans‐ 3 ). Specifically, two enzymes from our in‐house metagenomic collection of oxidoreductases, IS2‐SDR and Dm7α‐HSDH, catalyzed the kinetic resolution of the starting racemic ketone 1 or its complete conversion into two diastereomeric products, respectively. Moreover, the kinetic resolution of the racemic cis ‐alcohol (2 ) was very efficiently obtained (E≅2.000) by lipase PS catalyzed acetylation in dry acetone. All the products were isolated with ee≥95 %. Simple chemical elaborations of some of them allowed to isolate the missing enantiomers. Abstract : A combination of different enzymatic activities and chemical protocols were exploited to access the two enantiomers of Wieland‐Miescher ketone and three of its four alcohols derivatives as enantioenriched species. Specifically, the optimization of biotransformations of WM‐ketone or of substrates (bio)chemically‐prepared from it, mediated by hydroxysteroids dehydrogenases, short chain alcohol dehydrogenases and lipases, are described.